How to Gain the Most from Structural Conditionality of IMF-Supported Programs - Andritzky, Jochen (IMF Working Papers; Working Paper ;, 2021)
Structural conditionality of IMF-supported programs is designed to support structural reforms by countries borrowing from the IMF. Taking stock of program conditions and their implementation, this paper finds that conditionality focuses on fiscal, monetary and financial issues-areas where IMF expertise is strong-and shies away from structural areas such as labor or product market reforms. Hence, tackling deep-rooted structural issues during IMF-supported programs often remained elusive. To ensure countries gain most from IMF conditionality, the paper outlines an evaluation matrix for prioritizing and designing structural reforms, and applies it to case studies.